2008
DOI: 10.1675/1524-4695(2008)31[70:eohaob]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Human Activity on Behavior of Breeding American Oystercatchers, Cumberland Island National Seashore, Georgia, USA

Abstract: About This Report For More InformationThis report examines underlying and emerging trends that are shaping the coast, coastal resources and uses, and coastal management and policy. Past and projected trends are presented in population and settlement; economic activity; social values; resources; environmental quality; hazards; and governance and management. An effort is made to use enough contextual information so that the data convey a story about the present and future of the nation's coasts. AcknowledgmentsM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
15
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 27 publications
2
15
0
1
Order By: Relevance
“…We observed no signs of diurnal predation on chicks during three years of study in this system (Thibault 2008). Also, attendance rates averaging 80% along the Waterway suggest that parents were not attempting to reduce attendance as a means to distract predators (Sabine et al 2008). In contrast, we did observe adults actively guarding chicks throughout the chick-rearing phase and this is consistent with observations from Safriel (1985) and Sabine et al (2008) who both observed vigilance throughout chick-rearing in Eurasian and American oystercatchers, respectively.…”
Section: Bulls Bay Waterwaysupporting
confidence: 87%
See 1 more Smart Citation
“…We observed no signs of diurnal predation on chicks during three years of study in this system (Thibault 2008). Also, attendance rates averaging 80% along the Waterway suggest that parents were not attempting to reduce attendance as a means to distract predators (Sabine et al 2008). In contrast, we did observe adults actively guarding chicks throughout the chick-rearing phase and this is consistent with observations from Safriel (1985) and Sabine et al (2008) who both observed vigilance throughout chick-rearing in Eurasian and American oystercatchers, respectively.…”
Section: Bulls Bay Waterwaysupporting
confidence: 87%
“…For example, chick growth and fledging success are related to the level and pattern of parental attendance during chick-rearing in Eurasian and North American Black oystercatcher (Haematopus ostralegus and H. bachmani, respectively;Ens et al 1992;Hazlitt et al 2002). However, to date, research that has considered parental attendance in American Oystercatchers has focused primarily on studies of the effects of human disturbance on parent behavior (McGowan and Simons 2006;Sabine et al 2008) and therefore our understanding of this behavior is limited.…”
mentioning
confidence: 99%
“…Vehicle use on beaches also resulted in the loss of at least three eggs and three chicks. losses of eggs and chicks due to human activities on beaches, including those involving dogs and vehicles, have been observed in other studies of shorebirds (e.g., Buick & Paton 1989;Patterson et al 1991;Marchant & Higgins 1993;leseberg et al 2000;lafferty et al 2006;Sabine et al 2008). …”
Section: Other Causes Of Mortalitysupporting
confidence: 58%
“…Active human disturbance includes activities such as walking on the shoreline, using a motorbike on or near the shore, swimming, shellfishing, boating, or bait digging (Antos et al 2007). The effects of active disturbance on wading birds have been examined; for example several studies have determined appropriate buffer zones for protecting foraging birds from disturbance (Rodgers and Smith 1997;Rodgers and Schwikert 2002;Sabine et al 2008). Passive human disturbance results from development and urbanization of coastal areas and can include the degradation and loss of habitats, impaired water quality conditions, loss of buffer vegetation (e.g., trees and shrubs), eutrophication resulting from increased nutrient inputs, and increased sedimentation and surface water flow.…”
Section: Introductionmentioning
confidence: 99%